Power to the People? Populism and the Politics of School Choice in the United States. Issue 1 (2nd January 2021) - Singer, Jeremy
ABSTRACT: I use the definition of populism as a discursive frame to consider the extent to which the politics of school choice in the United States have been populist. This analysis offers a novel way to understand how political actors have forged coalitions to support school choice and suggests how they may remake their positions in an evolving political context. Populist approaches in the politics of school choice have been muted over the past three decades, as the contemporary educational reform movement has relied on political rhetoric that would foster and maintain broad-based coalitional support for its agenda. This is revealed by the dominant framing of school choice in the contemporary reform era, and by its contrast with more populist discourses throughout the politics of school choice. While populist sentiments are rising in the United States, political elites largely still rely on the contemporary reform movement's weakly populist or elitist discourse surrounding school choice. Social and geographic divisions within and between political constituencies remain obstacles to a populist turn in the politics of school choice.